2011
DOI: 10.1038/jhh.2011.58
|View full text |Cite
|
Sign up to set email alerts
|

White blood cell subsets are associated with carotid intima-media thickness and pulse wave velocity in an older Chinese population: the Guangzhou Biobank Cohort Study

Abstract: Cross-sectional associations between white blood cell (WBC) count, lymphocyte and granulocyte numbers, and carotid intima-media thickness (IMT) and brachialankle pulse wave velocity (PWV) were examined in a novel older Chinese community sample. A total of 817 men and 760 women from a sub-study of the Guangzhou Biobank Cohort Study had a full blood count measured by an automated hematology analyzer, carotid IMT by B-mode ultrasonography and brachial-ankle PWV by a non-invasive automatic waveform analyzer. Follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 41 publications
1
16
0
Order By: Relevance
“…The relation between the ba-PWV with the leukocyte subtype counts is not clear. In the same line as our results, Kavousiet al [ 4 ] found that ba-PWV was not correlated with monocyte count, whereas Phillips et al [ 11 ] found that leukocyte count (β = 0.07; p < 0.001) and granulocyte number (β = 0.07; p < 0.001) were significantly positively related to ba-PWV in a Chinese population, but not lymphocyte number. Bearing in mind these opposite results, it is considered as necessary to carry out more prospective studies in order to elucidate the association between ba-PWV and leukocyte subtype counts and the differences that could be observed in each gender.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The relation between the ba-PWV with the leukocyte subtype counts is not clear. In the same line as our results, Kavousiet al [ 4 ] found that ba-PWV was not correlated with monocyte count, whereas Phillips et al [ 11 ] found that leukocyte count (β = 0.07; p < 0.001) and granulocyte number (β = 0.07; p < 0.001) were significantly positively related to ba-PWV in a Chinese population, but not lymphocyte number. Bearing in mind these opposite results, it is considered as necessary to carry out more prospective studies in order to elucidate the association between ba-PWV and leukocyte subtype counts and the differences that could be observed in each gender.…”
Section: Discussionsupporting
confidence: 90%
“…Several studies have demonstrated that neutrophils have an important role in the atherosclerosis development in the general population [ 10 , 43 ] and in men [ 7 ]. The monocytes are correlated with the IMT in healthy subjects [ 5 , 11 ] and in Japanese subjects with type 2 diabetes [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The result indicated CTRP3 influences systemic inflammation possibly mainly in hypertensive, not obese subjects. The WBC count has been considered as a marker of cardiovascular disease risk measured through indicators of atherosclerosis and arterial stiffness in previous data [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…The leukocyte count has been reported to correlate with coronary heart disease (CHD) since 1920s [2]. In addition, many epidemiologic studies have reported that an increased leukocyte count is a strong and independent risk factor for cardiovascular events [3][4][5][6][7][8][9][10] and for the prevalence and progression of subclinical carotid atherosclerosis [11][12][13][14][15][16], suggesting that leukocyte count is useful as a clinical marker to predict atherosclerotic diseases. On the other hand, leukocyte count includes several types of cells which have different participation form in atherogenesis.…”
Section: Introductionmentioning
confidence: 99%